2016
DOI: 10.1016/j.postharvbio.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Browning inhibition and microbial control in fresh-cut persimmon (Diospyros kaki Thunb. cv. Rojo Brillante) by apple pectin-based edible coatings

Abstract: Keywords:Minimally processed persimmon Edible coatings Antimicrobial agents Sensory and microbial quality Food-borne human pathogens Shelf life A B S T R A C TThe aim of this study was to develop new edible coatings based on apple pectin with a combination of antioxidants and antimicrobial agents to control enzymatic browning and microbial growth of fresh-cut 'Rojo Brillante' persimmon. The survival of important food-borne human pathogens artificially inoculated on fresh-cut fruit was also assessed. Potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 31 publications
2
33
2
1
Order By: Relevance
“…In addition, the higher CO 2 transmission coefficient and lower O 2 transmission coefficient during NSCC coating create a better microenvironment with low oxygen and high carbon dioxide to reduce fruit respiration rate and further delay senescence [24]. Limiting microbial load is also a critical factor to delay senescence and increase the shelf life of the fruits [25]. The antibacterial activity of the coating treatments was analyzed against two typical foodborne pathogenic microbes, E. coli and S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the higher CO 2 transmission coefficient and lower O 2 transmission coefficient during NSCC coating create a better microenvironment with low oxygen and high carbon dioxide to reduce fruit respiration rate and further delay senescence [24]. Limiting microbial load is also a critical factor to delay senescence and increase the shelf life of the fruits [25]. The antibacterial activity of the coating treatments was analyzed against two typical foodborne pathogenic microbes, E. coli and S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…한국식품저장유통학회지 제26권 제4호 (2019) 372 or the produces are stored in modified atmospheric conditions (11)(12)(13)(14)(15)(16).…”
Section: Introduction 1)unclassified
“…The use of natural polymers assists in the development of materials with rapid biodegradability and greater compatibility with product, besides the possibility of its consumption together with the food, as fruits and vegetables minimally processed. 2,3,[8][9][10] Studies have shown that the development of films or coatings can maintain quality and increase shelf life of minimally processed carrots during storage, with colour maintenance and reduction mass loss 2 ; carotenoid content (trans-α-carotene e trans-β-carotene) during drying of pumpkin slices at 70°C (8-10 hours) 11 ; inhibition browning in freshcut persimmon 12 ; postharvest quality of red peppers 13 ; and increase of freshly cut pineapple stability. 14 Edible films and coatings besides the basic functions, and compatibility with food, can also be carriers of active compounds, known as active films.…”
mentioning
confidence: 99%